Minorities in Croatia and the Challenges of Multiculturalism - Mesić, Milan (Array, 2004)
The paper is an attempt in arguing that contemporary Croatia is a multicultural, but not (yet) multiculturalist society, since national minority rights are conceived as additive rights rather than transformative ones. At the same time, the author doubts that some of the ethnic groups on the list of officially recognized (22) minorities can met any reseonable minority definition.